EMPLOYEES’ ABILITY IN USING COMPUTER TERMINOLOGY AT SEI RENGAS II URBAN VILLAGE OFFICE, MEDAN - Ika Swantika; Puteri F. Addini; Kristin L. Sitompul; M. Rifan Afandi; Eko Sutanto (English Language Teaching Prima Journal (ELT), 2026)
The rapid development of information technology has encouraged the digital transformation of public services, requiring government employees to understand and use computer terminology effectively. This study aimed to analyze employees’ ability in using computer terminology and identify factors influencing their understanding. A quantitative descriptive method was employed. The population consisted of all employees at Sei Rengas II Urban Village Office, Medan, and total sampling was applied. Data were collected through questionnaires, interviews, and observations and analyzed using descriptive statistics. The findings revealed that most employees experienced improvements in their understanding and application of computer terminology after receiving training. Approximately 60% of employees improved their competency category, while 40% showed score improvements but remained in the same category. The